Extending opportunities how active social policy can benefit us all (Organisation for Economic Co-operation and Development, 2005)
Social policy is often disparaged as being a burden on society, but this book attempts to show that well-designed social protection can be an asset that is critical for sustaining social development. It maintains that to fulfill that potential, however, social protection now needs to recognize new needs of individuals and families, and new constraints on their functioning. Successful programs will require new means to attain their goals, to leverage the initiatives of a broad range of actors, and to involve clients at every stage in the design and delivery of programs. In examining these questions, this report stresses the importance of shifting the focus of social programs from insuring individuals against a few, well-defined contingencies towards investing in their capabilities and making use of them to the best of their potential at every stage of the life course. It also underscores the importance of broadening the roles played by individuals, employers and trade unions, as well as profit and not-for-profit providers of social services. The book opens with an assessment of the situation in OECD countries, comparing levels of poverty, social isolation, and social spending and indicators such as fertility rates, divorce rates, and distribution of household types (single, single parents, couples without children, couples with children). In the second part, issues relating to families and children are explored, with data provided on gender gaps in employment and earnings, time spent by men and women on child care, maternity and parental leave, and family poverty. The third part of the book examines poverty among prime-aged persons and includes extensive information on social assistance and disability. The final part examines social issues faced by older people and includes information on employment of older people, effective ages of retirement in different countries, training of older employees, pensions, and long-term care.